Synergistic Role of Teachers and Parents in Performing the Character Building of Students at SMA 3 Denpasar - I Wayan Darna; Nyoman Dantes; I Gusti Ngurah Sudiana (Cetta: Jurnal Ilmu Pendidikan, 2023)
The synergy of the roles of teachers and parents affects toward the development of children's character starting from the family, school to their community. This study aims to illustrate the optimization towards the role of teachers and parents in the developing of discipline, responsibility, simplycity and family characteristics to the students at SMA 3 Denpasar. This descriptive qualitative employes the teachers, parents, and principals as the research subjects. The data was collected through interviews and observations techniques which were analyzed thoroughly using analyz interacative model technique, in addition to using the triangulation to test the data validity. The results showed that the optimization of the roles of teachers and parents can be conducted by: 1) building effective communication between parents and teachers; 2) conducting periodic meetings between teachers and parents; 3) Involving parents in school anniversary celebrations.